Resilience and professional identity among young healthcare workers in a Shanghai megahospital during COVID-19: a cross-sectional study - Xu, Di; Zhou, Yaxu; Yan, Yuru; Wang, Yan; Le, Ye; Ma, Yuchun; Wang, Chunming; Zhou, Ying (Frontiers in Public Health, 2025)
BackgroundPublic health crises such as the COVID-19 pandemic place immense psychological and professional pressure on healthcare workers, particularly those early in their careers. While much research has focused on burnout and stress, fewer studies have examined the role of professional identity and its organizational determinants among actively employed young healthcare professionals.MethodsThis cross-sectional study surveyed 326 young healthcare workers (≤40 years old) across clinical, research, and administrative roles in a megahospital in Shanghai, China. A validated multidimensional scale was used to assess professional identity. Independent variables included job satisfaction, workload, exposure to high-risk duties, and perceived organizational support (including satisfaction with humanistic care and working conditions). Descriptive statistics, Mann–Whitney U and Kruskal-Wallis H tests, and multivariate linear regression were employed.ResultsThe majority of respondents (92.9%) reported a high level of professional identity (median score: 81, IQR: 13). Satisfaction with humanistic care (B = 3.431, p = 0.009) and working conditions (B = 3.679, p = 0.003) were strong predictors of higher professional identity scores. Significant differences in professional identity were observed based on gender, income satisfaction, and exposure to COVID-19 patients.ConclusionThis study highlights the essential role of organizational resources—particularly perceived humanistic care and adequate working conditions—in sustaining professional identity among young healthcare professionals during public health emergencies. The findings underscore the need for system-level interventions that support resilience and workforce stability. These insights may inform global strategies for healthcare human resource management in high-pressure contexts.